2015
DOI: 10.1186/s12887-015-0494-5
|View full text |Cite
|
Sign up to set email alerts
|

Parental knowledge, attitudes and practices regarding antibiotic use for acute upper respiratory tract infections in children: a cross-sectional study in Palestine

Abstract: BackgroundIn primary health care centres, upper respiratory tract infections (URTIs) in children are commonly encountered by physicians. Viruses cause most URTIs, but parents’ attitudes often represent an important reason for antibiotic abuse, which leads to the development and spread of antimicrobial resistance. The goal of this study was to examine parents’ knowledge, attitudes, and practices (KAP) about antibiotic use for children with URTIs in Palestine.MethodsA cross-sectional study was performed in prima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
84
2
9

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(106 citation statements)
references
References 46 publications
(50 reference statements)
11
84
2
9
Order By: Relevance
“…Our findings are largely in line with those of previous studies on parental beliefs about antibiotics' benefits for acute respiratory infections, [18][19][20][21][22][23][24][25][26] although our study is among the first to quantify them. Of course, such expectations were not homogeneous across parents and illnesses-parents knew that not using antibiotics is sometimes acceptable, consistent with previous findings.…”
supporting
confidence: 82%
See 2 more Smart Citations
“…Our findings are largely in line with those of previous studies on parental beliefs about antibiotics' benefits for acute respiratory infections, [18][19][20][21][22][23][24][25][26] although our study is among the first to quantify them. Of course, such expectations were not homogeneous across parents and illnesses-parents knew that not using antibiotics is sometimes acceptable, consistent with previous findings.…”
supporting
confidence: 82%
“…27,28 About one-half of parents reported antibiotic resistance as a potential harm, similar to proportions found in other cross-sectional studies, 21,28,29 although there was confusion among many about what resistance actually was, as has been reported by others. 18,25,29 Fewer parents mentioned common antibiotic harms consistent with empirical evidence, such as diarrhea and candidiasis 30 , and some of the complications that parents nominated as being reduced by antibiotic use are not clearly supported by evidence from randomized trials. Parents reported widespread use of alternatives to antibiotics in line with previous findings, 18,23 most of which have no or weak empirical evidence of efficacy, 31,32 with the exceptions being analgesics and antipyretics, and honey for cough.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, 76.4% of PNU students used antibiotics prescribed by doctor while small percentage (3.1%) consumed antibiotics preparation available at home. Another study in Palestine by Zyoud et al, 2015, showed that only 18.9 % of parents thought that antibiotics did not have any harmful side effects. In our study, 77.2% of PNU students disagreed that it is allowed to stop using antibiotics if its harm and benefit equals while22.8% agreed with that idea.…”
Section: Discussionmentioning
confidence: 99%
“…Both bacteriological and viral microorganisms are etiological factors contributing to the development of upper respiratory tract infections 1 . However, most of them are caused by viruses, in which antibiotics are not needed 2,3,4 . Respiratory system conditionsare the most common cause for antibiotics prescription 5,6 .Several studies showed that physicians practice in prescribing antibiotics in such cases could be related to the physician response to the patient pressure 7,8,9 .In addition, over-prescription practices have been attributed to vague diagnosis and the fear of inadequate level of health care.Antibiotics misuse in cases where no definite clinical benefits from them can lead to adverse effects 10,11,12 .…”
Section: …………………………………………………………………………………………………… Introduction:-mentioning
confidence: 99%